2020
DOI: 10.3390/ma13163457
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Approach of GRA Coupled with Principal Component Analysis for Multi-Optimization of Shielded Metal Arc Welding (SMAW) Process

Abstract: Welding distortion is a critical issue as it leads to severe deterioration of structural integrity of welded work piece and dimensional precision. This study aims at studying the effects of shielded metal arc welding (SMAW) parameters on the evolution of mechanical properties, including tensile strength, impact toughness, and hardness, along with angular distortion on a welded joint from SA 516 grade 70. Such parameters are analyzed and optimized by employing the Taguchi method and Grey relational analysis. SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…ANOVA suitability was analyzed using a normal distribution of residuals. As shown in Figure 5, the residuals for all responses, i.e., Ra, Fc, TW, and MRR, fall near the fitted line and were therefore normally distributed [43]. Additionally, the Anderson-Darling test for normality further confirms that the data were normality distributed for all responses as the test's p-values were greater than 0.05.…”
Section: Development Of Models For Responses and Analysis Of Variance...mentioning
confidence: 59%
“…ANOVA suitability was analyzed using a normal distribution of residuals. As shown in Figure 5, the residuals for all responses, i.e., Ra, Fc, TW, and MRR, fall near the fitted line and were therefore normally distributed [43]. Additionally, the Anderson-Darling test for normality further confirms that the data were normality distributed for all responses as the test's p-values were greater than 0.05.…”
Section: Development Of Models For Responses and Analysis Of Variance...mentioning
confidence: 59%
“…Qazi et al integrated a methodology of GRA combined with primary component analysis (PCA) for the optimization of the shielded metal arc welding (SMAW) technique of steel plates SA 516 grade 70. The authors studied the effect of SMAW specifications on the transformation of mechanical characteristics [ 35 ]. They reported that the experiments display acceptable agreement with optimum outcomes.…”
Section: Related Workmentioning
confidence: 99%
“…µ 𝑖 (k) is the grey relational coefficient, m is the identification/distinguishing coefficient that is usually set to 0.5 [25]. δ 𝑚𝑖𝑛 and δ 𝑚𝑎𝑥 are the minimum and maximum deviations of each response variable.…”
Section: Gray Relational Coefficient and Gray Relational Gradementioning
confidence: 99%